P08.37 Epidemiological trends in chlamydia testing in denmark 1991 to 2011 and formation of a retrospective, population-based cohort: the danish chlamydia study. (13th September 2015) - Turner, KME; Frølund, M; Davies, B; Benfield, T; Rasmussen, S; Ward, H; May, MT; Westh, H; Andersen, BS; Bangsborg, J; Christiansen, CB; Dessau, RBC; et al.
Abstract : Background: Despite widespread, sustained testing for chlamydia in high income countries, there remain questions about the population impact of chlamydia screening. We analyse the epidemiological trends in chlamydia testing and chlamydia diagnoses in Denmark (1991 to 2011) and describe cases and controls for The Danish Chlamydia Study. Methods: We describe the Danish Chlamydia Study; a unique database of individuals involving linkage of administrative health data, chlamydia tests and hospital records. We analyse trends in testing and diagnosed incidence of chlamydia and selected reproductive outcomes in men and women in Denmark. The laboratory dataset contained 4, 150, 498 test records from 1, 348, 058 individuals (1/1/1991 to 2/11/2011). Cases: individuals with a positive chlamydia diagnosis; controls: age and gender matched, selected from Danish population register. The proportion ever tested and test positivity were calculated by age, gender and calendar year. Results: The cleaned laboratory dataset (1 confirmed test result per person, per day) consists of 3, 298, 104 test records with 264, 410 (8%) positive chlamydia diagnoses. 1, 277, 463 individuals were tested (346, 235 men and 904, 587 women). Nearly all women and almost half of men in Denmark have been tested for chlamydia by age 30. Most individuals had only negative tests: 80% of men and 86% of women. Test coverage has increased and been sustained since 2008 but there has been no decline in positivity over time. Individuals included in the Danish Chlamydia Study dataset: Women: 574, 679 (114, 936 cases, 459, 743 controls (279, 905 only negative tests, 179, 838 never tested)), contributing 1, 807, 618 tests and 20, 912 reproductive outcomes; Men: 325, 337 (65, 068 cases, 260, 269 controls) contributing 291, 655 tests and 9, 698 reproductive outcomes. Conclusion: This large, rich dataset including long term follow up of a nationally representative sample of men and women from Denmark is a step forward in addressing some of the outstanding questions about the population impact of chlamydia screening.